Postpartum Implanon/Nexplanon continuation rates and associated factors among women who ever used Implanon/Nexplanon in a tertiary hospital in Accra, Ghana - Mumuni, Kareem; Asah-Opoku, Kwaku; Ganu, Vincent; Samba, Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum Implanon use serves as an important conduit to bridge the wide gap of unmet need for contraception. The study sought to determine the continuation rates of postpartum Implanon/Nexplanon use and factors associated with it. Methods: A retrospective review of electronic data of 391 women who had received postpartum Implanon/Nexplanon insertions from January 2012 to December 2015 was conducted at a family planning hospital in Accra, Ghana. Continuation rates and factors associated with discontinuation at 6 months, one year and two years post-partum were determined. Data were analysed using IBM Statistical Package for Social Science (SPSS) version 20. Results: A total of 391 postpartum Implanon/Nexplanon insertions were done during study period. Their mean age was 28.51±5.29 years and median parity was 2.0. Continuation rates of postpartum Implanon/Nexplanon at 6 months, 1 year and 2 years post uptake were 94.9%, 92.8% and 86.4% respectively. Women with tertiary level education were 64% less likely to continue Implanon/Nexplanon use at one-year post uptake (OR=0.36, CI=0.16-0.85). Women with education up to Senior High School were 62% less likely to continue postpartum Implanon/Nexplanon use at 2 years after uptake (OR=0.38, CI=0.18-0.81). Women between ages 20 and 29 years were 53% less likely to continue postpartum Implanon/Nexplanon use at 2 years (OR=0.47, CI=0.26-0.86). Reasons for discontinuation of postpartum Implanon/Nexplanon use were wishes to get pregnant and side effects of the method. Conclusions: Post -partum Implanon/Nexplanon continuation rates are high and remain as a viable choice for reduction of unplanned pregnancies post- delivery.